2000
DOI: 10.1017/s0033291799001828
|View full text |Cite
|
Sign up to set email alerts
|

The power and omnipotence of voices: subordination and entrapment by voices and significant others

Abstract: This study suggests that the power imbalance between the individual and his persecutor(s) may have origins in an appraisal by the individual of his social rank and sense of group identification and belonging. The results also raise the possibility that the appraisal of voice frequency and volume are the result of the appraisal of voices' rank and power. Theoretical and novel treatment implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
352
1
15

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(411 citation statements)
references
References 26 publications
(30 reference statements)
41
352
1
15
Order By: Relevance
“…The plan of the described therapy was developed taking into account four theoretical sources: (1) cognitive behavioural approach to psychotic symptoms [9,10], (2) cognitive theory of auditory hallucinations [11][12][13][14], (3) theory of relationships between hallucinations and the person experiencing these hallucinations [15][16][17], and (4) the use of computer software to create an avatar, in this case an avatar of auditory hallucinations [4,7]. Cognitive models of psychotic disorders assume that appraisals and beliefs play an important role in the creation and persistence of psychotic symptoms.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…The plan of the described therapy was developed taking into account four theoretical sources: (1) cognitive behavioural approach to psychotic symptoms [9,10], (2) cognitive theory of auditory hallucinations [11][12][13][14], (3) theory of relationships between hallucinations and the person experiencing these hallucinations [15][16][17], and (4) the use of computer software to create an avatar, in this case an avatar of auditory hallucinations [4,7]. Cognitive models of psychotic disorders assume that appraisals and beliefs play an important role in the creation and persistence of psychotic symptoms.…”
Section: Purposementioning
confidence: 99%
“…Early work from Paul Chadwick and Max Birchwood [11] showed that beliefs about 'voices' , specifically regarding identity, power, intention and control, are the key to understanding emotional consequences of the symptom, which are difficult to deal with by the patient. In his later work, Birchwood [13,14] integrated the cognitive model of auditory hallucinations with the relational approach, in which persons hearing voices through the beliefs about voices evaluate their position in the category of domination or subordination. Most often, they perceive 'voices' as powerful and themselves as weak, which makes them subordinate to voices.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a signifi cant relationship has been found between how hearers of voices experience relationships with others in their everyday life (for example, as relatively powerless, inferior and subordinate), and how they also experience their voices powerlessly, and as subordinate to them (Birchwood, Meaden, Trower, Gilbert, & Plaistow, 2000;Birchwood et al, 2004). Beyond the personal situation itself, it may be that the voices refl ect the social atmosphere of the era in question.…”
Section: Resituating Hallucinations In the Context Of The Person And mentioning
confidence: 99%
“…Although the idea of removing that which distresses is logical, and functions in many settings, it does not always work where private events-such as voices or intrusive thoughts-are concerned (García-Montes, Pérez-Álvarez, & Fidalgo, 2003, 2004, and avoidance or reaction just tend to exacerbate such experiences, giving rise to the ironic effect that the person has more of the same. In sum, as shown by the work of Birchwood et al, the distress arising from the activity of voices can be understood by reference to the individual's relationship with the voice, rather than voice content, topography or illness characteristics alone (Birchwood & Chadwick, 1997;Birchwood, Meaden, Trower, & Plaistow, 2000 (Beck & Rector, 2004;Gaudiano, 2005;Temple, 2004), which has shown itself to be effective in reducing the transition to psychosis in people at ultra-high risk, becoming proposed as an acceptable alternative to antipsychotic medication (Morrison, French et al, 2004, 2007. Likewise, cognitive-behavioural therapy has emerged as effective in changing beliefs about the power and omnipotence of the voices and in reducing the distress and depression associated with them, and hence in reducing compliance (Farhall et al, 2007;Trower et al, 2004).…”
Section: Resituating Hallucinations In the Context Of The Person And mentioning
confidence: 99%